PENGARUH KONSORSIUM AZOSPIRILLUM, AZOTOBACTER DAN BAKTERI PELARUT FOSFAT TERHADAP PERTUMBUHAN TANAMAN PADI - Wuriesyliane, Wuriesyliane (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2017)
Swamp land in South Sumatra has a huge potential to be developed. In order to utilize the good microorganisms to help increase plant growth and production, has done a lot of research on soil microbes. When microbes inoculated into rhizosfir they can have a positive impact (mutualism or komensalisme), the negative impact (parasitism, competition or amensalisme) or did not give any imluence (neutralism). The aim of this research was to studied the effect of consortium bacterial isolates growth of rice plants as well as to obtain best composition of Azotobacter, Azospirilium and phosphate solubilizing bacteria in spurring growth of rice plants. This research was conducted in October 2012 to February 2013. The results showed that treatment C (Azotobacter and BPF) can increase vegetative growth or rice plants and can increase the content of N and P in soil.